Toward an integrated project complexity narrative – A case study of academic organizations. Issue 5 (19th May 2022) - Fossum, Knut Robert; Honoré‐Livermore, Evelyn; Veitch, Erik; Haskins, Cecilia; Palmer, Erika K.
Abstract: The last decade has seen a growing interest in the benefits of applying project management (PM) and system engineering (SE) in an integrated way toward complex projects and programs. The concept of project complexity dimensions, with roots in both disciplines, is suggested as a component of an integrated project complexity narrative. This paper investigates how such a project complexity narrative is reflected when informants talk about the role of PM and SE in two academic organizations. Most informants address uncertainty and social‐political risks as part of their work, but any consistent use of a project complexity narrative is related to environmental and technical systems. The findings also indicate difficulty differentiating between the concepts of complicated and complex. The paper further contemplates how these findings inform efforts to manage complex research projects and programs.